Clinical outcome of adding injection of freeze-dried platelet-derived factor concentrate to operative treatment accompanied by an early rehabilitation for Achilles tendon rupture in high-level athletes - Shota Morimoto; Futoshi Morio; Yuta Matsumae; Masashi Nakamura; Yoshitaka Nakao; Toshiya Tachibana; Tomoya Iseki (Regenerative Therapy)
Background: Achilles tendon ruptures (ATRs) often occur in competitive athletes. Various studies have been conducted to improve the treatment outcomes for ATRs, but the results remain unsatisfactory for athletes. Purpose: To review our experiences of adding injections of freeze-dried platelet-derived factor concentrate (FD-PFC) to surgical treatment with an early rehabilitation for ATRs in high-level athletes. Methods: We retrospectively analyzed 8 high-level athletes (Tegner activity score ≥8) with ATR, who received postoperative injection of FD-PFC in addition to surgical treatment with an early rehabilitation protocol between May 2019 and November 2021. In all patients, surgery was performed using the modified side-locking loop suture technique, and an early rehabilitation protocol was implemented postoperatively. The prepared FD-PFC was injected into the Achilles tendon suture site under ultrasound guidance at 4 weeks postoperatively. Evaluation of the clinical outcomes included the following factor: the American Orthopedic Foot and Ankle Society ankle-hindfoot scale (AOFAS) score measured preoperatively and at one year postoperatively, time to ability to perform 20 continuous double- and single-leg heel raises (DHR/SHR), time to return to the original sport, and complications related to surgery or FD-PFC injection. In addition, magnetic resonance imaging (MRI) was performed for all patients at 12 and 24 weeks postoperatively to evaluate Achilles tendon maturation. Results: The 8 patients consisted of 7 males and one female athletes with a mean age of 28.5 ± 5.2 years (range, 23–39 years) at the time of surgery. All patients were high-level athletes with a mean Tegner activity score of 9.0 ± 0.5 (range, 8–10). The mean AOFAS score improved significantly from 36.0 ± 9.4 preoperatively to 96.8 ± 3.6 at one year postoperatively (p < 0.001). The mean time to be able to perform 20 continuous DHR and 20 continuous SHR was 6.8 ± 0.8 weeks and 10.1 ± 1.6 weeks, respectively. All patients could return to their original sport at pre-injury levels with the mean time of 18.3 ± 2.7 weeks. Also, there were no complications related to surgery or injection. Furthermore, T2-weighted MRI showed the high signal intensity of the sutured tendon in 25 % (2 of 8 patients) at 12 weeks and 0 % (0 of 8 patients) at 24 weeks postoperatively. Conclusions: The addition of FD-PFC injections to surgical treatment with an early rehabilitation protocol could provide satisfactory results for high-level athletes with ATRs, enabling them early return to their original sports at pre-injury level. This treatment option may be useful for athletes with ATRs.